2017
DOI: 10.1051/0004-6361/201629693
|View full text |Cite
|
Sign up to set email alerts
|

Dusty globules in the Crab Nebula

Abstract: Context. Dust grains are widespread in the Crab Nebula. A number of small dust concentrations are visible as dark spots against the background of continuous synchrotron emission in optical images. Aims. Our aim is to catalogue such roundish, dusty globules and investigate their properties. Methods. From existing broad-band images obtained with the Hubble Space Telescope, we located 92 globules, for which we derived positions, dimensions, orientations, extinctions, masses, proper motions, and their distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
(74 reference statements)
4
9
1
Order By: Relevance
“…Using an increased AV /NH ratio more appropriate for the Crab Nebula, and a total extinction within the range found by Grenman et al (2017) for Crab Nebula dusty globules, we find that models with nH = 1900 cm −3 reproduce the observed ArH + and OH + surface brightnesses measured by Barlow et al (2013), while underpredicting the H2 surface brightness compared to Loh et al (2010Loh et al ( , 2011Loh et al ( , 2012 Gomez et al (2012), although surface brightness ratios are comparable with observed values. We suggest that these dusty globules are the source of most of the observed molecular emission in the Crab Nebula, with denser gas accounting for the ∼ 10% of globules associated with H2 vibrational emission.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Using an increased AV /NH ratio more appropriate for the Crab Nebula, and a total extinction within the range found by Grenman et al (2017) for Crab Nebula dusty globules, we find that models with nH = 1900 cm −3 reproduce the observed ArH + and OH + surface brightnesses measured by Barlow et al (2013), while underpredicting the H2 surface brightness compared to Loh et al (2010Loh et al ( , 2011Loh et al ( , 2012 Gomez et al (2012), although surface brightness ratios are comparable with observed values. We suggest that these dusty globules are the source of most of the observed molecular emission in the Crab Nebula, with denser gas accounting for the ∼ 10% of globules associated with H2 vibrational emission.…”
Section: Discussionsupporting
confidence: 68%
“…The globule sizes range from 6×10 15 cm to 3 × 10 16 cm, similar to the sizes of the H2 emitting knots observed by Loh et al (2011), although Grenman et al (2017) note that only ∼ 10% of their dusty globules are coincident with H2 knots. While the observed globule sizes are similar to our nH = 1900 cm −3 model cloud thicknesses, none of our preferred models match the extinctions found by Grenman et al (2017). These models used a standard interstellar AV /NH ratio of 6.289 × 10 −22 cm 2 mag, whereas with the increased dust-to-gas ratio in the Crab Nebula the true value is likely to be higher.…”
Section: Filament Size and Extinctionsupporting
confidence: 73%
See 3 more Smart Citations